Application of Socrative-Based Assessment to Measure Mathematical Creative Thinking Ability with Problem Based Learning Model Viewed from Curiosity (Unnes Journal of Mathematics Education, 2022)
The study aims to (1) test whether the Problem Based Learning model with the application of Socrative-based assessment was effective for measuring students' mathematical creative thinking abilities and (2) describe mathematical creative thinking ability in terms of curiosity in Problem Based Learning model with the application of Socrative-based assessments. The research was included in the mix-method with a sequential explanatory design. The results showed that (1) Problem Based Learning with the application of Socrative assessment was said to be effective for measuring students' mathematical creative thinking abilities; (2) a description of students' mathematical creative thinking ability in terms of curiosity, it was found that students with a high level of curiosity were able to meet the indicators of creative thinking ability elaboration, originality, fluency, and flexibility and were able to explain how to solve smoothly with logical reasons, and students with a medium level of curiosity meeting the indicators of creative thinking ability of elaboration, fluency, and flexibility and being able to explain how to solve it smoothly with logical reasons, and students with a low level of curiosity fulfilling the indicators of creative thinking ability of elaboration and fluency and less able to explain how to solve it smoothly with logical reasons.